The Impact of Work Pressure on the Performance of Workers in Light of the Corona Pandemic – An Applied Study at the Libyan Center for Biotechnology Research (Journal of human and social sciences, 2024)
This study aimed to identify the impact of work pressure on the performance of workers during the Corona pandemic at the Libyan Center for Biotechnology Research. Seventy-five questionnaires were distributed, and 48 were retrieved, with a response rate of 60%. The results showed a statistically significant effect of work pressure on workers' performance. The study recommended developing plans and strategies to alleviate these pressures in the future.
Keywords: Work pressures; sources of stress; Corona pandemic; work environment